A emergência de uma sociologia gorda como uma sociologia do transborde : implicações das corporalidades gordas para o pensamento contemporâneo - Arandas, Luciana Pionório Rocha de (2023)
This study relies upon the intertwining of the existing academic production on/about the body and the most recent discussion on feminist theory, by ways of virtual ethnography as a methodological tool, while considering online social networks as the research territory, and Instagram as its particular locus, and seeking to answer how the performance strategies of fat women on the internet break the social standards established for their existence. The guiding questions proposed here are the following: when women´s fat activisms operate their performances, what do they seek to establish? Is there a new aesthetic / ethics they are willing to push forth? What are they managing to implement? In short, the analysis proposed here looks back into “to whom” or “in favor of what” is fat activism being built? This central questioning, in turn, brought out the main thesis of the research: that the classic studies within the Sociology of the Body, and its canons, do not account for the complex specificity of the fat body. Studies on the fat body, supported by the Sociology of the Body, still delimit their analyses on diseases/health issues (focused mostly on obesity), on aesthetics (through the bias of beauty standards) and, last but not least, on gender issues (focused mainly on the impact of fat on women and their social lives). This slicing/splitting up of the fat body as a study object ends up revealing a crueller face of sociology towards fat bodies, one that reinforces the erasure of their wholeness, loosing site of their human condition, which differs from the idea of a laboratory animal to be unravelled for scientific purposes. Such problem, which seems to be rooted in a central methodological issue, can be better understood through the analysis of Fat Dissident´s performance strategies, taking it as a specificity of activism within anti-fatphobia struggles taking place online through social networks. The question of class is also considered as a landmark category capable of operating the differentiations for and between fat people. To this end, an issue that is already imposed as a starting point of this study, refers to the analysis of the fat body in its complexity of layers that overlap all these aspects widely studied by the Sociology of the Body in a separate, split up way. The theoretical impulse that emerges from the analysis of the activism of fat women on social networks online, is taking as an example what happened in the research on the black body, when the studies on race/color established their own field, to account for the specificities of women experiences lived by black people. Henceforth, the research proposed here has two objectives: (i) to study activism within the issues of social networks (Instagram) and, (ii) to analyse, as a theoretically important and innovative approach, the intricate workings of a Fat Sociology as a Sociology of Transborder.